Studi Optimalisasi Pelayanan Bus Damri Bandara Sultan Hasanuddin - Herawati, Herawati; Mutharuddin, Mutharuddin (Warta Penelitian Perhubungan, 2010)
Sultan Hasanuddin Airport is one of the transport nodes that have an important role in ensuringeffective implementation of inter-mode transport and efficient. To realize that goal PT Damri providesairport buses as a service alih nwde to improve accessibilihj to and from the airport. However, theavailabilihJ of the airport is not opti"mal due to limited available fleet and a route served has not beenable to reach the entire cihJ of Makassar and surroundings. In this research, an analysis of theoptimization efforts airport bus at Sultan Hasanuddin Airport.T7ie metlwd used is descriptive quantitative metlwd with a review of the operations and sclieduling.T7ie analysis was divided into 3 phases, namely analysis of the performance of the e:risting airport buswith reference to the standard indicators of the Department of Transportation public transportationservice, the identification of tlie origin and destination wnes potential using maximum entropi; methodand analysis of the needs of the fleet.Based on tlie analysis of the data obtained that tlie level of bus service Hassanuddin Sultan InternationalAirport as one of the integrator nwdes are still at the level of being. According to the analysis results canidentify potential zone is a zone 2 witli tlie needs of a fleet of 4 and 14-minute headwm;, zone 7 witli tlieneeds of a fleet of 72 units and headwm; 4 minutes, zone 8 units with 45 units and fleet needs 6 minuteslieadwm;. Based on tliese zones, tlie airport bus service as a nwde of transportation than can re VJJ.timizedbiJ increasing the service area bi; 40%, 107% load factor and the communities served bi; 85%.